Illocutionary Speech Act Analysis of Kageyama Tobio in the Anime Movie Haikyuu the Dumpster Battle - Ariansyah, Dava; Ali, ​Mohammad (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The research aims at analyzing language events in Japanese mass media with respect to ilocutionary speech acts that appear in conversations involving the main character Kageyama Tobio from Haikyuu The Dumpster Battle (2024). For the purpose of collecting the information, the researcher uses qualitative descriptive methodology relying on note taking as the tool for data gathering in authentic texts related to the character’s discourse. Moreover, the arc are classified using Searle’s typology and assessed with respect to their pragmatic aspects. Namely, attention will be paid to revealing the roles of speech acts performed by the character int the course of a very dynamic game of volleyball, when communication server both as a means of achieving some strategic goals and of fosteribg good interpersonal realtions between players. From the findings, it can be seen that among other speech act categories the most frequent one is directive acts because the role played by the character in question requires him to be a leader of the team. Moreover, expressive acts reveal an important pragmatic development of the character because their number suggests his emotional maturity.